2009
DOI: 10.5194/bgd-6-4865-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of increased <i>p</i>CO<sub>2</sub> and temperature on trace element (Ag, Cd and Zn) bioaccumulation in the eggs of the common cuttlefish, <i>Sepia officinalis</i>

Abstract: Abstract. Cephalopods play a key role in many marine trophic networks and constitute alternative fisheries resources, especially given the ongoing decline in finfish stocks. Along the European coast, the eggs of the cuttlefish Sepia officinalis are characterized by an increasing permeability of the eggshell during development, which leads to selective accumulation of essential and non-essential elements in the embryo. Temperature and pH are two critical factors that affect the metabolism of marine organisms in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 47 publications
4
19
0
Order By: Relevance
“…One might therefore predict greater metal toxicity in organisms with exposure under higher pCO 2 . This hypothesis is supported by the observed influence of increased pCO 2 on the bioaccumulation of trace metals in the eggs and embryos of the squid Loligo vulgari (Lacoue-Labarthe et al, 2011 and eggs of the cuttlefish Sepia officinalis (Lacoue-Labarthe et al, 2009). While these studies have measured bioaccumulation, the only current study to investigate the influence of OA on metal toxicities showed increased toxicity of Cu, but not Cd, to the copepod Amphiascoides atopus under conditions of elevated pCO 2 (Pascal et al, 2010).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…One might therefore predict greater metal toxicity in organisms with exposure under higher pCO 2 . This hypothesis is supported by the observed influence of increased pCO 2 on the bioaccumulation of trace metals in the eggs and embryos of the squid Loligo vulgari (Lacoue-Labarthe et al, 2011 and eggs of the cuttlefish Sepia officinalis (Lacoue-Labarthe et al, 2009). While these studies have measured bioaccumulation, the only current study to investigate the influence of OA on metal toxicities showed increased toxicity of Cu, but not Cd, to the copepod Amphiascoides atopus under conditions of elevated pCO 2 (Pascal et al, 2010).…”
Section: Introductionsupporting
confidence: 57%
“…OA is expected to alter the bioavailability of water-borne metals (Millero et al, 2009). The toxic free-ion concentration of metals such as copper (Cu) may increase by as much as 115% in coastal waters in the next 100 years due to reduced pH (Pascal et al, 2010;Richards et al, 2011), whereas the free-ion concentration of other metals including cadmium (Cd) may decrease or be unaffected (Lacoue-Labarthe et al, 2009, 2011Pascal et al, 2010). One might therefore predict greater metal toxicity in organisms with exposure under higher pCO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The premature hatching observed here may be a response to hypoxia (Kamler, 2008), as a decrease in the oxygen flux (by means of diffusion) leads to egg swelling and, consequently, greater surface area and reduced egg wall thickness (Cronin and Seymour, 2000;Lacoue-Labarthe et al, 2009;Wolf et al, 1985). Swelling does not prevent P O2 from consistently falling (to critical levels) and P CO2 from rising within cephalopod eggs (Gutowska and Melzner, 2009;Rosa et al, 2013c).…”
Section: Discussionmentioning
confidence: 96%
“…Up and down regulation of genes associated with various pathways during exposure to ocean acidification suggests an organisms effort to compensate for the effects of elevated pCO 2 [81]. There have also been studies which highlight the variability in the potential ecotoxicological consequences associated with elevated CO 2 accumulation of metals varied; 110m Ag increased and 109 Cd decreased with decreasing pH, whereas 65 Zn accumulation was highest at pH 7.85, but lower at pH 7.6 than 8.1 (control, [71]) in the cuttlefish Sepia officinalis.…”
Section: Mechanisms In Echinoderms and Molluscsmentioning
confidence: 99%
“…For example, there was no effect on calcification rates, size or weight in juveniles of the grooved carpet clam Ruditapes decussates raised at pCO 2 of 1694 and 4245 ppm (pH 7.84 and 7.46 respectively), but mortality was reduced in acidified treatment (pH 7.46), possibly due to delayed reproductive development of clams preventing spawning in acidified treatments [69] as an energy saving survival strategy. Also in contrast to the other molluscs with mainly planktotrophic larvae, the lecithotrophic juvenile European cuttlefish, Sepia officinalis, which hypercalcify, similar to some teleost fish and decapod crustaceans, showed no adverse growth or developmental effects with significantly more CaCO 3 accreted into cuttlebones [70] and eggs increased in weight [71] when raised at elevated pCO 2 . Of the few studies to investigate the synergistic impacts of elevated pCO 2 (600, 750, 1000 ppm, mean pH 8.02, 7.95 and 7.83 respectively) and temperature (18, 22, 26 and 30 °C), Parker et al [39] found impacts on larval development including reduced development, size and increased abnormality in D veliger larvae and spat for both Crassostrea gigas and Saccostrea glomerata were exacerbated as did Lischka et al [66] in the polar pteropod, Limacina helicina.…”
Section: Molluscsmentioning
confidence: 99%